2016
DOI: 10.1021/acs.est.6b04500
|View full text |Cite
|
Sign up to set email alerts
|

Complete Nitrogen Removal from Synthetic Anaerobic Sludge Digestion Liquor through Integrating Anammox and Denitrifying Anaerobic Methane Oxidation in a Membrane Biofilm Reactor

Abstract: Partial nitritation and Anammox processes are increasingly used for nitrogen removal from anaerobic sludge digestion liquor. However, their nitrogen removal efficiency is often limited due to the production of nitrate by the Anammox reaction and the sensitivity to the nitrite to ammonium ratio. This work develops and demonstrates an innovative process that achieves complete nitrogen removal from partially nitrified anaerobic sludge digestion liquor through the use of a membrane biofilm reactor (MBfR), with met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 46 publications
4
82
0
Order By: Relevance
“…Methanoperedens-like archaea at a rate of 57 mg N L −1 day −1 and the total nitrogen removal efficiency of the culture was as high as 97.5%. The rates for ammonium and nitrite removal reported here are amongst the higher rates for anammox/N-damo cultures (Allegue et al 2018; Liu et al 2019; Luesken et al 2011a, 2011b; Shi et al 2013; Xie et al 2017a, b). Yet, as in these previous studies, it was shown that in a mixed anammox/N-damo culture, the presence of Ca.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Methanoperedens-like archaea at a rate of 57 mg N L −1 day −1 and the total nitrogen removal efficiency of the culture was as high as 97.5%. The rates for ammonium and nitrite removal reported here are amongst the higher rates for anammox/N-damo cultures (Allegue et al 2018; Liu et al 2019; Luesken et al 2011a, 2011b; Shi et al 2013; Xie et al 2017a, b). Yet, as in these previous studies, it was shown that in a mixed anammox/N-damo culture, the presence of Ca.…”
Section: Discussionmentioning
confidence: 48%
“…Methylomirabilis-like bacteria and Ca. Methanoperedens-like archaea can be cultured together in laboratory-scale membrane reactors, together removing methane, ammonium, nitrite, and nitrate from the influent (Ding et al 2017; Lu et al 2017; Shi et al 2013; Xie et al 2017a, b). In addition to cooperation, these organisms may also compete with each other under substrate limitation (Luesken et al 2011a, 2011b; Arshad et al 2017; Guerrero-Cruz et al 2019; Welte et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As a possible solution to the poor CH 4 mass transfer issue, our group has previously proposed the use of hollow fibre membranes (HFMs) to supply CH 4 gas in membrane biofilm reactors (MBfRs) driving denitrification, resulting in an increase in the denitrification performance by 20-30 times relative to a control [21,22]. This significant improvement can be understood by considering that in MBfRs, methanotrophic biofilm colonize and grow on the outer surface of the membranes, having therefore direct access to CH 4 at supersaturation levels.…”
Section: Introductionmentioning
confidence: 99%
“…These membrane processes provide a better control over the cultivation of microorganisms as well as allow a higher quality of effluent and a smaller bioreactor footprint. 67 For P removal, MBR coupled with a biological process known as enhanced biological phosphorous (Bio-P) have demonstrated good P removal efficiency for tertiary wastewater treatment. 68 However, no direct work on the treatment of anaerobic effluents has been reported for these processes so far to our knowledge.…”
Section: Membrane-coupled Bioprocesses For Nutrients Removalmentioning
confidence: 99%